Feedbacks Between Ocean Productivity and Organic Iron Complexation in Reaction to Changes in Ocean Iron Supply - Völker, Christoph; Ye, Ying (Frontiers in Marine Science, 2022)
Low concentrations of iron, an important micronutrient for photosynthetic organisms, limit growth in large parts of the ocean. The solubility and availability of iron is to a large degree determined by organic iron-binding molecules, so-called ligands. While ligands come from a variety of sources, many of them are produced in autotrophic or heterotrophic production in the ocean, leading to the possibility of feedbacks between marine primary production and iron availability. The diversity of ligands, reaching from siderophores, small molecules involved in bacterial iron uptake, to breakdown products and long-lived macromolecules like humic substances, means that feedbacks could be both negative and positive or there may even be no feedback at all. Here we investigate first, how the cycling of this ligand pool can be described simplistically in a model such that it reproduces the observed global distribution of dissolved iron and phosphorus as closely as possible. We show that inclusion of a ligand similar to refractory dissolved organic carbon leads to an improved agreement to observations in our model. Inclusion of a second, shorter-lived siderophore-like ligand does not strongly affect this agreement. In a second step we then study how feedbacks affect how iron distribution and oceanic productivity react to changes in external supply of iron. We show that, to be consistent with present-day iron distribution, the dominant feedback is positive, increasing the sensitivity of global biological productivity and hence carbon cycling to changes in iron supply. The strength of the feedback increases with increasing ligand life-time. The negative feedback associated with siderophore-like ligands has the potential to mitigate the positive feedback, especially at the surface and for global export production, but more research on the production and decay of siderophores is needed for a better quantification. Ocean biogeochemical models that assume a constant ligand concentration and hence neglect possible feedbacks may therefore underestimate the reaction of the global carbon cycle to the strong increase in dust deposition under future or glacial climate conditions.